한국 중년여성의 전곡류 섭취수준과 영양소 섭취 및 대사적 위험지표의 연관성 - 김예진(Ye Jin Kim); 염진희(Jin Hee Yum); 이승민(Seung Min Lee) (Korean journal of community nutrition, 2014)
Objectives: Epidemiological studies have suggested that a higher consumption of whole grain foods can significantly reduce the risk of chronic diseases including cardiovascular diseases, type 2 diabetes and obesity. The objective of the current study was to examine associations among the consumption of whole grains and nutrient intakes and biochemical indicators associated with chronic diseases among generally healthy middle-aged Korean women. Methods: Using 24-hour recall data from the 2008-2009 National Health and Nutrition Examination Surveys, whole grain intake (g/day) was calculated for a total of generally healthy 1,953 subjects. The subjects were divided into three groups by the level of whole grain consumption (0 g/day, > 0 and < 20 g/day or ${≥}20g/day$). Mean values or proportions of various nutrient intakes and metabolic risk factors were compared according to the level of whole grain consumption. All statistical analysis was conducted using SAS software version 9.2. Results: We observed that the overall consumption of whole grains was quite low. Specifically, 58.2% of subjects reported no whole grain consumption on the day of the survey, and the mean whole grain intake was only 15.3 g/day. The whole grain consumption was positively associated with intakes of various macro and micronutrients, namely, plant proteins and fats, dietary fiber, calcium, plant iron, potassium, zinc, vitamin A, ${β}$-carotene, thiamin, riboflavin, niacin, vitamin $B_6$ and folic acid. In addition, we found significantly decreasing trends in abdominal obesity and hypertriglyceridemia as whole grain intake levels increase. Conclusions: The study findings suggested the importance of promoting whole grain consumption as an efficient tool for improving various dietary aspects and preventing chronic diseases.